RAHNER’S ‘ANTHROPOLOGICAL TURN’ IN THEOLOGY AND DOCTRINE OF REVELATION - Xavier, Joseph (Asian Horizons, 2014)
The article attempts to revisit Rahner’s understanding of divine revelation in the light of man’s transcendental openness to the Absolute Mystery called God. Therefore, first, it briefly analyses the anthropological presuppositions of Rahner’s theology centred on the concept of ‘supernatural existential.’ Thereafter, it attempts to see how the transcendental enquiry is indeed a ‘theological’ investigation and what are the philosophical-theological bases for his claim that man is fundamentally capax infiniti for God. It explores how the transcendental openness of man is linked to the Christian idea of revelation, both in grace and in history. Finally, it wants to see how Rahner understands the culmination of revelation in the Christ event is actualised in the Word of God and what are its implications for contemporary theology.